Funciones desempeñadas como monitor de calidad en el servicio en caja municipal de ahorro y crédito de Piura (Período 2015-2018) - Cancino Vargas, Carl Denys (2018)
During the period 2015 - 2018 I have served as Quality Service Monitor in the Savings and Loan Municipal Savings Bank of Piura. This position is created in 2015 within the marketing area as a process that supports the strategies of placements and fund raising of the company. Below, I present a summary of my professional experience. The first chapter of the report shows general information about the company, its history, its organizational strategy and institutional values. In detail the expansion process is shown, the portfolio of products and services that it has. In this same section, I present the environment where Caja Piura operates, the main regulatory aspects that influence its activities and the Caja Municipales system. Finally, I make known the new customer-oriented approach and the leading and important role it has in companies as well as the structural organization chart of the company and the functions of the position held. In the second chapter, the theoretical framework gives us the main concepts related to quality of service, highlighting those of level of satisfaction and level of net recommendation. In this part, Caja Piura develops its ad hoc Model with its own definitions of its attributes and the necessary components to ensure the correct implementation of a new customer-focused service culture. Finish this chapter with a critical analysis of the functions performed during the professional experience. The third chapter presents a summary of the functions of the position, the activities carried out, as well as personal contributions and achievements during the professional experience. As a result, a diagnosis is presented with the main quality indicators of the first quarter of 2017 and the opportunities for improvement identified qualitatively. Finally, the fourth chapter shows the critical assessment of university education, some conclusions and final recommendations.